Traditionally Used Plants in the Treatment of Diabetes Mellitus: Screening for Uptake Inhibition of Glucose and Fructose in the Caco2-Cell Model - Katharina Schreck; Matthias F. Melzig (Frontiers Media S.A., 2021)
The traditional use of plants and their preparations in the treatment of diseases as a first medication in the past centuries indicates the presence of active components for specific targets in the natural material. Many of the tested plants in this study have been traditionally used in the treatment of Diabetes mellitus type 2 and associated symptoms in different cultural areas. Additionally, hypoglycemic effects, such as a decrease in blood glucose concentration, have been demonstrated in vivo for these plants. In order to determine the mode of action, the plants were prepared as methanolic and aqueous extracts and tested for their effects on intestinal glucose and fructose absorption in Caco2 cells. The results of this screening showed significant and reproducible inhibition of glucose uptake between 40 and 80% by methanolic extracts made from the fruits of Aronia melanocarpa, Cornus officinalis, Crataegus pinnatifida, Lycium chinense, and Vaccinium myrtillus; the leaves of Brassica oleracea, Juglans regia, and Peumus boldus; and the roots of Adenophora triphylla. Furthermore, glucose uptake was inhibited between 50 and 70% by aqueous extracts made from the bark of Eucommia ulmoides and the fruit skin of Malus domestica. The methanolic extracts of Juglans regia and Peumus boldus inhibited the fructose transport between 30 and 40% in Caco2 cells as well. These findings can be considered as fundamental work for further research regarding the treatment of obesity-correlated diseases, such as Diabetes mellitus type 2.